In vitro evaluation of α-amylase inhibitory activity of some medicinal plants used in treatment of diabetes mellitus in Algeria and their effect on postprandial hyperglycemia in normal rats - Asma BECHIRI; Echaimaa CHEKROUN; Rachid AZZI; Rabah DJAZIRI (International Journal of Phytomedicine, 2015)
Postprandial hyperglycemia is an early defect of type 2 diabetes, it is responsible of secondary complication which can affect many organs: heart, kidney, nervous system, and impaired their function. In this type of diabetes mellitus, the inhibition of digestive enzymes (α-amylase and α-glucosidases) is a useful treatment to attenuate postprandial hyperglycemia. In this study we investigate in vitro, the α-amylase inhibitory potential of aqueous extract of leaves or roots of five selected plants recommended to treat diabetes in traditional Algerian medicine. They are also tested for their effect on reduction of postprandial hyperglycemia induced by starch loading in normal rats. The plant extracts showed a variable degree of inhibition of α-amylase. The most active sample is the aqueous extract of Phylleria angustofolia (PaE) with an IC50=0.61mg/ml followed by extract of Olea europea (OeE), Juniperus oxydrus (JoE), Olea europea var. Sylvestris (OsE) and Salvia officinalis (SoE). Acarbose (Acb), a standard inhibitor, exhibited an IC50 value of 0.07mg/ml. In an animal study, two plant extracts and acarbose exhibited an anti-hyperglycemic activity: SoE and PaE suppress significantly postprandial hyperglycemia response induced by starch loading in rats, as shown by the significant attenuation of the value of AUC0-180min by 60٪ (p<0.05) for PaE, 48٪ (p<0.05) for SoE and34٪ (p<0.05) for Ac, compared to control group. These findings suggest that among the five medicinal plants studied, Phylleria angustifolia and Salvia officinalis exert their antidiabetic effect by inhibition the digestion of complex carbohydrates, retarding glucose absorption and hence suppress postprandial hyperglycemia.